Patent foramen ovale closure in stroke patients with migraine in the CLOSE trial. The CLOSE‐MIG study. (16th June 2021) - Mas, Jean‐Louis; Guillon, Benoît; Charles‐Nelson, Anaïs; Domigo, Valérie; Derex, Laurent; Massardier, Evelyne; Arquizan, Caroline; Vuillier, Fabrice; Timsit, Serge; Béjot, Yannick; Detante, Olivier; Sablot, Denis; et al.
Abstract: Background and purpose: The efficacy of patent foramen ovale (PFO) closure to reduce the frequency of migraine attacks remains controversial. Methods: This was a planned sub‐study in migraine patients enrolled in a randomized, clinical trial designed to assess the superiority of PFO closure plus antiplatelet therapy over antiplatelet therapy alone to prevent stroke recurrence in patients younger than 60 years with a PFO‐associated cryptogenic ischaemic stroke. The main outcome was the mean annual number of migraine attacks in migraine patients with aura and in those without aura, as recorded at each follow‐up visit by study neurologists. Results: Of 473 patients randomized to PFO closure or antiplatelet therapy, 145 (mean age 41.9 years; women 58.6%) had migraine (75 with aura and 70 without aura). Sixty‐seven patients were randomized to PFO closure and 78 to antiplatelet therapy. During a mean follow‐up of about 5 years, there were no differences between antiplatelet‐only and PFO closure groups in the mean annual number of migraine attacks, both in migraine patients with aura (9.2 [11.9] vs. 12.0 [19.1], p  = 0.81) and in those without aura (12.1 [16.1] vs. 11.8 [18.4], p  > 0.999). There were no differences between treatment groups regarding cessation of migraine attacks, migraine‐related disability at 2 years and use of migraine‐preventive drugs during follow‐up. Conclusions: In young and middle‐aged adults with PFO‐associated cryptogenic stroke and migraine, PFO closure plus antiplatelet therapy did not reduce the mean annual number of migraine attacks compared to antiplatelet therapy alone, in migraine patients both with and without aura. Abstract : In young and middle‐aged adults with PFO‐associated cryptogenic stroke and migraine, PFO closure plus antiplatelet therapy did not reduce the mean annual number of migraine attacks compared to antiplatelet therapy alone, both in migraine patients with and without aura.